2016
DOI: 10.1111/hel.12367
|View full text |Cite
|
Sign up to set email alerts
|

The importance of TH22 and TC22 cells in the pathogenesis of Helicobacter pylori‐associated gastric diseases

Abstract: Increased Th22, Tc22, and Tc22/17 cells and IL-22 levels appear to be influential in progression and severity of H. pylori infection. Th22/17 can be an interesting therapeutic target for chronic H. pylori infections where eradication is more difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…Our outcomes indicated that TNF-α mRNA expression in H. pylori-infected patients was higher in comparison with that of H. pylori negative patients. These ndings are in agreement with previous reports that the TNF-α expression has been demonstrated to increase in the gastric mucosa of H. pylori-infected patients [31][32][33][34]. Several studies have demonstrated that polymorphisms in the TNF-α genes result in high transcriptional promoter activity along with increased gastric in ammation, which are related with an increased risk of H. pylorirelated GC and PUD developments [35,36].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our outcomes indicated that TNF-α mRNA expression in H. pylori-infected patients was higher in comparison with that of H. pylori negative patients. These ndings are in agreement with previous reports that the TNF-α expression has been demonstrated to increase in the gastric mucosa of H. pylori-infected patients [31][32][33][34]. Several studies have demonstrated that polymorphisms in the TNF-α genes result in high transcriptional promoter activity along with increased gastric in ammation, which are related with an increased risk of H. pylorirelated GC and PUD developments [35,36].…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to our detections, Shamsdin et al demonstrated that and noted no signi cant change in TNF-α serum levels in the infected patients with PUD and gastritis; however, the TNF-α serum levels in combination with IL-6 were found to be signi cantly higher in the gastritis patients as compared to the PUD patients. In addition, they observed signi cantly higher levels of TNF-α in the active chronic and chronic gastritis patients as compared to the uninfected groups [33].…”
Section: Discussionmentioning
confidence: 94%
“…However, RA can enhance gap junction intercellular communication by increasing the expression of Cx43[126-128]. A previous study indicated that all-trans RA (ATRA) may inhibit gastric carcinoma tumor growth by targeting GC stem cells[129]; therefore, we predict that it may be mainly due to the effect of ATRA. The LPS-TLR4 signaling pathway has an important role in LPS-mediated disease.…”
Section: Cx43mentioning
confidence: 99%
“…IL‐22‐producing T cells have previously been implicated in the pathogenesis of H. pylori infection . Shamsdin et al . analyzed subsets of IL‐22 + T cells in human peripheral blood mononuclear cells.…”
Section: Immunologymentioning
confidence: 99%
“…IL-22producing T cells have previously been implicated in the pathogenesis of H. pylori infection. 25 Shamsdin et al 26 Mezache et al 27 showed that PD-L1 is highly expressed in normal gastric mucosal biopsies and upregulated even further in H. pylori-infected tissue. The majority of PD-L1 + mononuclear cells were CD8 + , indicating that these cells play an important role in modulating the mucosal immune response.…”
Section: T Cells and Cytokinesmentioning
confidence: 99%